2004
DOI: 10.1063/1.1773378
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the spacer layer growth temperature on multilayer InAs∕GaAs quantum dot structures

Abstract: The growth temperature of spacer layers (SPLs) is investigated as a means to obtain identical layers for multilayer quantum dot (QD) structures. A 5-layer 1.3-μm InAs∕GaAs QD structure with 50-nm GaAs SPLs served as a model system. It is found that the growth temperature of the GaAs SPLs has pronounced effects on both the structural and optical properties of the InAs QDs. For GaAs SPLs grown at a low temperature of 510°C, dislocations are observed in the second and subsequent layers, a result of significant su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 20 publications
0
41
1
Order By: Relevance
“…The temperature was then decreased back to 510 C for the growth of the next DWELL. Areal dot densities of cm per layer were measured by atomic force microscopy on uncapped structures [4], [5]. The energy separation between ground and excited state transitions for this sample, as measured by PL spectroscopy, was 50 meV.…”
Section: Growth and Fabricationmentioning
confidence: 99%
“…The temperature was then decreased back to 510 C for the growth of the next DWELL. Areal dot densities of cm per layer were measured by atomic force microscopy on uncapped structures [4], [5]. The energy separation between ground and excited state transitions for this sample, as measured by PL spectroscopy, was 50 meV.…”
Section: Growth and Fabricationmentioning
confidence: 99%
“…However, stacking multiple QD layers modifies the growth of subsequent layers, which in the extreme results in defect formation as a consequence of the increasing amount of strained material deposited. Solutions include strain compensation [3], [4], removal of the largest dots by selective evaporation [5], and the use of high growth temperature spacer layers (HGTSLs) between QD sheets, which have recently been demonstrated to greatly enhance device characteristics in multilayer 1.3-m In(Ga)As QD lasers [6], [7]. This letter describes the measurement of gain and loss of five-layer QD laser material with and without HGTSLs to reveal the mechanisms responsible for this improvement.…”
mentioning
confidence: 99%
“…This GaAs layer is grown at an ele− vated temperature (590 o C), and is called a high growth tem− perature spacer layer (HGTSL). At this temperature, gal− lium adatoms have a high mobility which leads to plana− rising the growth front for subsequent layers [3,14]. It has been shown that a GaAs HGTSL can planarise QD growth front only if its thickness is greater than a critical limit [15,16].…”
Section: Resultsmentioning
confidence: 99%